A fuel cell composite catalyst, its preparation method and use
Patent Information
- Application Number
- CN202611297400.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-09
AI Technical Summary
通过铂和/或铂合金纳米颗粒的高催化活性、M-Nx位点的协同作用及氮掺杂有序介孔碳的结构优势,解决了传统Pt基催化剂成本高、稳定性差、传质效率低等痛点,是极具应用潜力的燃料电池阴极氧还原(ORR)催化剂
本发明提供的燃料电池复合催化剂包括活性载体以及负载的活性组分;活性载体包括M-N-C,N-C代表具有可配位N位点的氮掺杂有序介孔碳,M代表通过与所述N位点配位而负载在所述氮掺杂有序介孔碳上的金属元素,且M包括Mn和/或Fe;活性组分包括铂和/或铂与过渡金属形成的合金。通过Pt或铂合金纳米颗粒的高催化活性、M-Nx位点的协同作用及氮掺杂有序介孔碳的结构优势,解决了传统Pt基催化剂成本高、稳定性差、传质效率低等痛点,是极具应用潜力的燃料电池阴极氧还原(ORR)催化剂。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of proton exchange membrane fuel cell catalyst technology, and relates to a fuel cell composite catalyst, its preparation method and application. Background Technology
[0002] With the escalating global energy crisis, the development of efficient, clean, and sustainable new energy conversion technologies has become a global research hotspot. Proton exchange membrane fuel cells (PEMFCs), as a device capable of directly converting hydrogen energy into electrical energy, possess outstanding advantages such as high energy conversion efficiency, zero emissions, fast start-up speed, and low operating noise. They show broad application prospects in fields such as new energy vehicles, distributed power generation, and portable electronic devices, and are considered one of the most promising clean energy technologies of the future.
[0003] The performance of proton exchange membrane fuel cells (PEMFCs) hinges on the efficiency of the oxygen reduction reaction (ORR) at the cathode. This reaction is kineticly slow and has a high overpotential, requiring highly efficient catalysts to lower the reaction energy barrier and accelerate the reaction process. Therefore, catalysts are crucial materials for the commercialization of PEMFCs. For a long time, the precious metal platinum (Pt) has been the preferred catalyst for the ORR reaction due to its excellent oxygen adsorption, activation, and reduction capabilities, and is widely used in the cathodes of traditional proton exchange membrane fuel cells.
[0004] However, the large-scale application of Pt-based catalysts faces three major bottlenecks that severely restrict the commercialization of PEMFCs. First, Pt, as a scarce and precious metal, is expensive and has limited reserves. Its usage accounts for more than 30% to 40% of the total cost of fuel cells, significantly increasing the cost of battery manufacturing and becoming the primary obstacle to the commercialization of PEMFCs. Second, in the complex operating environment of PEMFCs, characterized by acidity, high potential, and strong oxidation, traditional pure Pt catalysts are prone to Pt nanoparticle migration, aggregation, and dissolution, leading to insufficient catalyst stability, shortened lifespan, and increased battery operation and maintenance costs. Third, pure Pt catalysts have limited mass transfer efficiency and are easily poisoned by toxic substances such as CO, further reducing catalytic activity and actual operational reliability, making them difficult to adapt to complex operating conditions. Summary of the Invention
[0005] In view of the problems existing in the prior art, the purpose of this invention is to provide a composite catalyst for fuel cells, its preparation method and uses. The composite catalyst includes an active support and a supported active component. The active support includes MNC, where NC represents nitrogen-doped ordered mesoporous carbon with coordinateable N sites, and M represents a metal element supported on the nitrogen-doped ordered mesoporous carbon through coordination with the N sites, and M includes Mn and / or Fe. The active component includes platinum and / or an alloy formed from platinum and transition metals. The high catalytic activity of platinum and / or platinum alloy nanoparticles, and the MNC... xThe synergistic effect of the sites and the structural advantages of nitrogen-doped ordered mesoporous carbon solve the pain points of traditional Pt-based catalysts, such as high cost, poor stability and low mass transfer efficiency, making it a fuel cell cathode oxygen reduction (ORR) catalyst with great application potential.
[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a fuel cell composite catalyst, comprising an active support and an active component loaded on the active support; the active support comprises MNC, wherein NC represents nitrogen-doped ordered mesoporous carbon having coordinateable N sites, M represents a metal element loaded on the nitrogen-doped ordered mesoporous carbon by coordination with the N sites, and M comprises Mn and / or Fe; the active component comprises platinum and / or an alloy formed of platinum and a transition metal.
[0007] Compared to precious metal Pt catalysts, microcrystalline carbon (MNC) catalysts (such as Fe-NC and Mn-NC) offer advantages such as low raw material cost, high atom utilization, and certain ORR catalytic activity. However, the intrinsic activity of a single MNC catalyst is still far lower than that of Pt-based catalysts. Therefore, this invention combines the active component platinum (such as Pt nanoparticles) with MNC materials, utilizing their synergistic effect to achieve "complementary advantages, increased efficiency, and reduced costs." In MNC, the use of mesoporous nitrogen-doped carbon support (NC) imparts a high specific surface area and an ordered porous structure to the catalyst, optimizing mass transfer efficiency and electron conduction performance. The resulting fuel cell composite catalyst effectively addresses the shortcomings of traditional Pt-based catalysts, such as high cost, poor stability, and low mass transfer efficiency, while also compensating for the insufficient activity of a single MNC catalyst.
[0008] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following technical solutions.
[0009] As a preferred embodiment of the present invention, the coordinateable N site includes pyridine N and / or pyrrole N.
[0010] Preferably, the mass of metal element M in the active carrier accounts for 3% to 10% of the mass of NC. For example, it can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10%, etc.
[0011] Preferably, the active component accounts for 20% to 60% of the mass of the fuel cell composite catalyst. For example, it can be 20%, 22%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, or 60%, etc.
[0012] In a second aspect, the present invention provides a method for preparing the fuel cell composite catalyst described in the first aspect, comprising: mixing MNC with active component raw materials in a liquid phase to obtain a mixture; wherein the active component raw materials include a platinum source, or include a platinum source and a transition metal source that forms an alloy with platinum; The reducing agent is mixed with the mixture to carry out a reduction reaction, thereby obtaining a fuel cell composite catalyst.
[0013] As a preferred embodiment of the present invention, the preparation method includes: dispersing MNC in a first dispersant to obtain a dispersion; dissolving the active component raw material in a first solvent to prepare an active component raw material solution; and adding the active component raw material solution dropwise to the dispersion for a second mixing to obtain the mixture. Pre-preparing the MNC into a non-agglomerated, uniform black dispersion allows for complete opening of the carrier pores, which is beneficial for the subsequent full adsorption of the Pt precursor. Adding the active component raw material solution dropwise to the dispersion helps prevent excessively rapid local reduction that could lead to particle agglomeration.
[0014] Preferably, the first dispersant comprises ethylene glycol.
[0015] Preferably, the concentration of MNC in the dispersion is 1 mg / mL to 5 mg / mL. For example, it can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, or 5 mg / mL, etc.
[0016] Preferably, the first solvent includes ethylene glycol.
[0017] Preferably, the temperature of the first mixture and the second mixture is 15℃~35℃ (i.e., room temperature), and the time is 8h~12h. For example, the temperature can be 15℃, 20℃, 25℃, 30℃, or 35℃, etc.; the time can be 8h, 9h, 10h, 11h, or 12h, etc. Thorough stirring is performed to ensure that the Pt ions fully interact with the carrier and are uniformly adsorbed, achieving a better impregnation effect.
[0018] Preferably, before the reduction reaction, the temperature is adjusted to 0℃~5℃ and the pH to 8~9. For example, the temperature can be 0℃, 1℃, 2℃, 3℃, 4℃, or 5℃, etc.; the pH can be 8, 8.2, 8.4, 8.6, 8.8, or 9.0, etc. The pH can be adjusted using a 0.05mol / L~0.15mol / L sodium hydroxide solution. A weakly alkaline environment can increase the reduction rate and improve the dispersibility of Pt particles.
[0019] Preferably, the reducing agent comprises sodium borohydride.
[0020] Preferably, the ratio of the molar amount of the reducing agent to the sum of the molar amounts of platinum and transition metal elements that alloy with platinum in the mixture is (8~10):1. For example, the ratio can be 8:1, 8.3:1, 8.5:1, 8.8:1, 9:1, 9.3:1, 9.5:1, 9.8:1, or 10:1, etc.
[0021] Preferably, the transition metal element of the transition metal source includes at least one of cobalt, nickel, iron, chromium, palladium, manganese, or copper.
[0022] Preferably, the reduction reaction takes 1 to 5 hours. For example, the time can be 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours.
[0023] Preferably, after the reduction reaction is completed, the catalyst is subjected to centrifugation, washing, drying and grinding in sequence to obtain the fuel cell composite catalyst.
[0024] Preferably, the cleaning includes washing with anhydrous ethanol and deionized water 3 to 5 times in sequence, for example, 3, 4 or 5 times.
[0025] Preferably, the drying method includes vacuum drying at 50℃~70℃ for 8h~16h. For example, the temperature can be 50℃, 55℃, 60℃, 65℃ or 70℃, etc.; the time can be 8h, 9h, 10h, 12h, 14h or 16h, etc.
[0026] As a preferred technical solution of the present invention, the method for preparing the MNC includes: providing nitrogen-doped ordered mesoporous carbon with coordinateable N sites, denoted as NC; performing a third mixing of NC and a metal M source in a liquid phase to carry out a coordination reaction to generate a precursor; subjecting the precursor to high-temperature annealing to obtain an annealed product; and subjecting the annealed product to acid washing, water washing, and drying to obtain MNC. In the coordination reaction, the metal M ions fully coordinate with the pyridine N and pyrrole N on the surface of NC to form an MN coordination intermediate (i.e., the precursor). High-temperature annealing can further stabilize the MN coordination bonds, forming a uniformly dispersed MN. xActive sites are identified, and carbon framework defects are repaired, enhancing support stability. Acid washing removes uncoordinated metal M ions, metal M oxides, and other inorganic impurities, while also facilitating further etching of the carbon framework to expose more MN. x Active site.
[0027] As a preferred embodiment of the present invention, the method for preparing the MNC includes: mixing NC with a second dispersant in a fourth mixing process to obtain a suspension; preparing a metal M source into an aqueous solution; and adding the aqueous solution of the M source dropwise to the suspension for a fifth mixing process to carry out the coordination reaction. Pre-preparing a uniform suspension helps ensure that the nitrogen-doped ordered mesoporous carbon is fully dispersed, exposing all pores and coordination sites.
[0028] Preferably, the second dispersant comprises water.
[0029] Preferably, the metal source M includes an iron source and / or a manganese source; the iron source includes at least one of ferric chloride, ferrous acetate, or ferric nitrate; and the manganese source includes at least one of manganese chloride and / or manganese acetate.
[0030] Preferably, the M source aqueous solution further includes 1 to 3 drops of 0.01 mol / L to 0.5 mol / L hydrochloric acid, for example, 1 drop, 2 drops or 3 drops, and the hydrochloric acid concentration can be 0.01 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L, etc.
[0031] Preferably, the coordination reaction is carried out at a temperature of 15℃ to 35℃, for a time of 6h to 12h, and at a stirring rate of 100rpm to 500rpm. For example, the temperature can be 15℃, 20℃, 25℃, 30℃, or 35℃, etc.; the time can be 6h, 8h, 10h, or 12h, etc.
[0032] Preferably, after the coordination reaction is completed, the precursor is evaporated to dryness to obtain the precursor.
[0033] Preferably, the drying method includes vacuum drying at 50°C to 70°C. For example, it can be 50°C, 55°C, 60°C, 65°C, or 70°C.
[0034] Preferably, the high-temperature annealing is carried out under an inert atmosphere, and the flow rate of the inert atmosphere is 80 mL / min to 120 mL / min; furthermore, before heating, continuous ventilation is carried out to completely remove the air from the tubular furnace to prevent the metal M ions from being oxidized.
[0035] Preferably, the heating rate of the high-temperature annealing is 1℃ / min to 10℃ / min, the holding temperature is 800℃ to 850℃, and the time is 1h to 2h. For example, the temperature can be 800℃, 810℃, 820℃, 830℃, 840℃, or 850℃, etc.; the time can be 1h, 1.3h, 1.5h, 1.8h, or 2h, etc.
[0036] Preferably, the pickling uses a sulfuric acid solution with a concentration of 0.2 mol / L to 0.8 mol / L. For example, it can be 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, or 0.8 mol / L, etc.
[0037] Preferably, the pickling temperature is 70℃~90℃, and the time is 2h~10h. For example, the temperature can be 70℃, 75℃, 80℃, 85℃ or 90℃, etc.; the time can be 2h, 4h, 6h, 8h or 10h, etc.
[0038] Preferably, the drying method includes vacuum drying at 60℃~80℃ for 6h~18h. For example, the temperature can be 60℃, 65℃, 70℃, 75℃ or 80℃, etc., and the time can be 6h, 8h, 10h, 12h, 14h, 16h or 18h, etc.
[0039] As a preferred technical solution of the present invention, the method for preparing NC includes: mixing a first template agent and a silicon source in a first liquid phase in a sixth process, performing a hydrothermal reaction, and then calcining the hydrothermal product in a first process to remove the first template agent, thereby obtaining ordered mesoporous silica; using the ordered mesoporous silica as a second template agent, mixing it with a nitrogen-doped carbon support in a seventh process in a second liquid phase, and then evaporating the solvent to obtain a composite precursor; pretreating the composite precursor and then performing a second calcination to achieve carbonization and in-situ nitrogen doping, thereby obtaining a calcined product; and mixing the calcined product with an alkaline solution in an eighth process, performing an etching reaction to remove the second template agent, thereby obtaining nitrogen-doped ordered mesoporous carbon.
[0040] As a preferred embodiment of the present invention, the first template agent comprises a poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer.
[0041] Preferably, the silicon source comprises tetraethyl orthosilicate.
[0042] Preferably, the solution of the first liquid phase comprises water and hydrochloric acid.
[0043] Preferably, the sixth mixing temperature is 30℃~40℃, and the time is 18h~36h. For example, the temperature can be 30℃, 33℃, 35℃, 38℃ or 40℃, etc.; the time can be 18h, 20h, 23h, 25h, 28h, 30h, 32h or 36h, etc.
[0044] Preferably, the hydrothermal reaction temperature is 100℃~150℃, and the time is 24h~48h. For example, the temperature can be 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃, etc.; the time can be 24h, 28h, 30h, 36h, 40h, 42h, 45h, or 48h, etc.
[0045] Preferably, the first calcination is carried out in an oxygen-containing atmosphere at a temperature of 300℃~600℃ for 3h~6h. For example, the temperature can be 300℃, 350℃, 400℃, 450℃, 500℃, 550℃ or 600℃, etc.; the time can be 3h, 4h, 5h or 6h, etc.
[0046] Preferably, the solution of the second liquid phase comprises water.
[0047] Preferably, the seventh mixing method includes ultrasonic dispersion.
[0048] Preferably, the pretreatment is carried out under a protective atmosphere at a temperature of 150℃~180℃ for 2h~3h. For example, the temperature can be 150℃, 155℃, 160℃, 165℃, 170℃, 175℃ or 180℃, etc.; the time can be 2h, 2.3h, 2.5h, 2.8h or 3h, etc.
[0049] Preferably, the second calcination is carried out under a protective atmosphere at a temperature of 600℃ to 900℃ for a time of 2h to 5h. For example, the temperature can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, or 900℃, etc.; the time can be 2h, 3h, 4h, or 5h, etc.
[0050] Preferably, the alkaline solution comprises a sodium hydroxide solution with a concentration of 1 mol / L to 2 mol / L.
[0051] Preferably, the etching reaction is carried out at a temperature of 60°C to 80°C for 6 hours to 12 hours, and a reflow treatment is performed. For example, the temperature can be 60°C, 65°C, 70°C, 75°C, or 80°C, etc.; the time can be 6 hours, 8 hours, 10 hours, 11 hours, or 12 hours, etc.
[0052] As a preferred embodiment of the present invention, the method for preparing the nitrogen-doped carbon support includes: reacting zinc salt with imidazole in a third liquid phase to obtain ZIF-8 powder; subjecting the ZIF-8 powder to a third calcination to obtain a pyrolysis product; and acid washing the pyrolysis product to obtain the nitrogen-doped carbon support. The third calcination of the ZIF-8 powder allows Zn to volatilize at high temperatures, leaving behind porous carbon with a high specific surface area. Simultaneously, N from the imidazole is in situ doped into the carbon framework, forming a large amount of pyridine N and pyrrole N that can provide coordination. Acid washing removes residual ZnO and inorganic impurities, and facilitates the generation of more defects and open pores, enhancing the exposure of surface nitrogen functional groups.
[0053] As a preferred embodiment of the present invention, the zinc salt includes zinc nitrate.
[0054] Preferably, the imidazole comprises 2-methylimidazole.
[0055] Preferably, the molar ratio of the zinc salt to the imidazole is 1:(3~5). For example, the ratio can be 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, etc.
[0056] Preferably, the solution of the third liquid phase comprises methanol.
[0057] Preferably, the third calcination is carried out under argon atmosphere at a temperature of 700℃ to 900℃. For example, the temperature can be 700℃, 750℃, 780℃, 800℃, 830℃, 860℃, or 900℃, etc.
[0058] Preferably, the pickling uses 0.1 mol / L to 1 mol / L sulfuric acid, the pickling temperature is 60℃ to 90℃, and the pickling time is 4h to 8h. For example, the concentration of sulfuric acid can be 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, or 1 mol / L, etc.; the temperature can be 60℃, 65℃, 70℃, 75℃, 80℃, or 90℃, etc.; and the time can be 4h, 5h, 6h, 7h, or 8h, etc.
[0059] Thirdly, the present invention provides a catalyst coating membrane, comprising a proton exchange membrane and a catalyst coating disposed on at least one side of the proton exchange membrane; the catalyst coating contains the fuel cell composite catalyst described in the first aspect, or contains the fuel cell composite catalyst obtained by the preparation method described in the second aspect.
[0060] Fourthly, the present invention provides a membrane electrode comprising the catalyst coating membrane described in the third aspect.
[0061] Fifthly, the present invention provides a fuel cell comprising the membrane electrode described in the fourth aspect.
[0062] It should be noted that, due to space limitations and to avoid redundancy, this invention does not exhaustively list all point values within the above numerical range, but it is not limited to the listed values either; other unlisted values within the above numerical range are also applicable.
[0063] Compared with existing technical solutions, the present invention has at least the following beneficial effects: The fuel cell composite catalyst provided by this invention includes an active support and a supported active component; the active support includes MNC, where NC represents nitrogen-doped ordered mesoporous carbon with coordinateable N sites, and M represents a metal element supported on the nitrogen-doped ordered mesoporous carbon through coordination with the N sites, and M includes Mn and / or Fe; the active component includes platinum and / or an alloy formed from platinum and transition metals. Through the high catalytic activity of Pt or platinum alloy nanoparticles, MNC... x The synergistic effect of the sites and the structural advantages of nitrogen-doped ordered mesoporous carbon solve the pain points of traditional Pt-based catalysts, such as high cost, poor stability and low mass transfer efficiency, making it a fuel cell cathode oxygen reduction (ORR) catalyst with great application potential. Detailed Implementation
[0064] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0065] Those skilled in the art will understand that the embodiments described are merely illustrative of the invention and should not be construed as limiting the invention.
[0066] Example 1 This embodiment provides a fuel cell composite catalyst, comprising an active support and an active component supported on the active support; the active support is MNC, and the active component includes Pt nanoparticles. The preparation method of this fuel cell composite catalyst includes: S10. Preparation of nitrogen-doped carbon support, including: S11. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol at a molar ratio of 1:4. Quickly pour the imidazole solution into the zinc salt solution, stir at room temperature for 24 h, centrifuge to collect the milky white precipitate, wash with methanol 3 times, and then vacuum dry at 60℃ for 12 h to obtain ZIF-8 powder. S12. ZIF-8 was placed in a tube furnace and calcined at 800°C under an argon (Ar) atmosphere for 2 hours. After natural cooling to room temperature, a black powder pyrolysis product was obtained. S13. Add the pyrolysis product to 0.5M H2SO4, stir at 80℃ for 6h for acid washing, then filter, and wash repeatedly with deionized water until the pH of the filtrate is 7. Then dry under vacuum at 60℃ for 12h to obtain nitrogen-doped carbon support. S20. Preparation of nitrogen-doped ordered mesoporous carbon (NC), including: S21. Dissolve the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in a mixture of deionized water and 2M HCl, and stir at 35°C until completely dissolved; then slowly add tetraethyl orthosilicate, and stir continuously for 24 hours before transferring to a hydrothermal reactor and reacting hydrothermally at 150°C for 24 hours. Then filter, wash with water, dry, and calcine in air at 500°C for 4 hours to obtain white powdery ordered mesoporous silica. S22. The nitrogen-doped carbon support obtained earlier was dispersed in deionized water, and then the obtained ordered mesoporous silica powder was added. After ultrasonic dispersion, the mixture was stirred for 12 hours to allow the nitrogen-doped carbon support to fully enter the mesoporous channels of silica. After evaporation in a water bath, the precursor / ordered mesoporous silica composite was obtained. The composite was pretreated at 160°C for 3 hours under a nitrogen (N2) atmosphere to allow the carbon source to initially polymerize. The temperature was then raised to 900°C and held under nitrogen protection for 3 hours to achieve carbonization and in-situ nitrogen doping. The product was cooled to room temperature to obtain the calcined product. S23. Add the calcined product to a 1 mol / L NaOH solution, reflux at 70°C for 8 h to dissolve the ordered mesoporous silica, centrifuge and filter repeatedly, wash with deionized water until neutral, and then vacuum dry to obtain a porous nitrogen-doped carbon support. S30. Preparation of Mn-NC catalyst, including: S31. Weigh 0.5g of the obtained nitrogen-doped ordered mesoporous carbon, add it to 50mL of deionized water, and sonicate it for 30min to form a uniform NC suspension; weigh 0.08g of Mn(Ac)2·4H2O, that is, the mass of the metal element Mn accounts for 3.58% of the mass of the nitrogen-doped ordered mesoporous carbon, dissolve it in 10mL of deionized water, add 2 drops of 0.1mol / L HCl solution, and stir until completely dissolved to obtain a transparent manganese source solution; S32. Slowly add the manganese source solution dropwise to the NC suspension, and magnetically stir at 300 rpm at room temperature for 9 hours to allow the Mn to settle. 2+ The precursor powder is formed by fully coordinating with the N sites of pyridine N, pyrrole N, etc. on the NC surface to form a Mn-N coordination intermediate. After stirring, the intermediate is transferred to a vacuum rotary evaporator and the solvent is evaporated under reduced pressure at 60°C to obtain the precursor powder. S33. Grind the obtained precursor powder evenly, put it into a ceramic boat, place it in a tube furnace, introduce argon gas at a flow rate of 100 mL / min, and continue to purge for 30 min to completely remove the air from the tube furnace. Set and run the heating program: heat to 800℃ at a rate of 5℃ / min, and hold at the temperature for 2 h for high-temperature annealing. S34. After annealing, turn off the heating device, keep the inert gas continuously flowing in, and let the tube furnace cool naturally to room temperature to obtain a black powdery annealing product. Transfer the cooled black powder to a beaker, add 40 mL of 0.5 mol / L H2SO4 solution, and stir in an 80°C water bath for 6 h. Then filter with a Buchner funnel, and wash the filter residue repeatedly with deionized water until the pH of the filtrate is 7 (tested with pH paper) to ensure that residual acid and impurities are completely removed. Then transfer the filter residue to a vacuum drying oven and vacuum dry at 70°C for 12 h. After grinding, a uniform black powder is obtained, which is the Mn-NC catalyst. S40. Preparation of composite catalysts for fuel cells, including: S41. Weigh 0.2 g of Mn-NC catalyst as the active support and place it in 60 mL of ethylene glycol. Disperse it ultrasonically at room temperature for 40 min to form a uniform black dispersion without agglomeration. Weigh 0.352 g of chloroplatinic acid (H2PtCl6·6H2O) according to the target Pt mass (loading) accounting for 40% of the mass of the fuel cell composite catalyst (i.e., the total mass of MCN and the supported active component). Dissolve it in 15 mL of ethylene glycol and stir until completely dissolved to obtain a Pt precursor solution. Slowly add the Pt precursor solution dropwise to the Mn-NC suspension. After the addition is complete, continue stirring at room temperature for 12 h to obtain a mixture. S42. Using an ice bath to control the system temperature at 0℃, add 0.1mol / L NaOH solution dropwise to the mixture to adjust the pH of the system to 8.5. Then, according to the molar ratio of Pt element to reducing agent NaBH4 of 1:8, prepare NaBH4 aqueous solution and slowly add it dropwise to the mixture to carry out the reduction reaction. Stir continuously during the dropwise addition process. After the dropwise addition is completed, remove the ice bath and continue stirring and reducing at room temperature for 3 hours. S43. After the reduction reaction is complete, centrifuge using a high-speed centrifuge, discard the supernatant, and collect the black solid at the bottom; wash repeatedly with anhydrous ethanol and deionized water four times by centrifugation to completely remove residual Cl. - Na + Impurities such as unreacted reducing agents were removed, and the filtrate was washed until it was neutral. The solid product was then transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours. After thorough grinding, the final composite catalyst powder was obtained.
[0067] Example 2 This embodiment provides a fuel cell composite catalyst, comprising an active support and an active component supported on the active support; the active support is MNC, and the active component includes Pt nanoparticles. The preparation method of this fuel cell composite catalyst includes: S10. Preparation of nitrogen-doped carbon support, including: S11. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol at a molar ratio of 1:4. Quickly pour the imidazole solution into the zinc salt solution, stir at room temperature for 24 h, centrifuge to collect the milky white precipitate, wash with methanol 3 times, and then vacuum dry at 60℃ for 12 h to obtain ZIF-8 powder. S12. ZIF-8 was placed in a tube furnace and calcined at 700°C under an argon (Ar) atmosphere for 3 hours. After natural cooling to room temperature, a black powder pyrolysis product was obtained. S13. Add the pyrolysis product to 0.5M H2SO4, stir at 90℃ for 6h for acid washing, then filter, and wash repeatedly with deionized water until the pH of the filtrate is 7. Then dry under vacuum at 60℃ for 12h to obtain nitrogen-doped carbon support. S20. Preparation of nitrogen-doped ordered mesoporous carbon (NC), including: S21. Dissolve the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in a mixture of deionized water and 2M HCl, and stir at 35°C until completely dissolved; then slowly add tetraethyl orthosilicate, and stir continuously for 24 hours before transferring to a hydrothermal reactor and reacting hydrothermally at 120°C for 36 hours. Then filter, wash with water, dry, and calcine in air at 500°C for 4 hours to obtain white powdery ordered mesoporous silica. S22. The nitrogen-doped carbon support obtained earlier was dispersed in deionized water, and then the obtained ordered mesoporous silica powder was added. After ultrasonic dispersion, the mixture was stirred for 12 hours to allow the nitrogen-doped carbon support to fully enter the mesoporous channels of silica. After evaporation in a water bath, the precursor / ordered mesoporous silica composite was obtained. The composite was pretreated at 160°C for 2.5 hours under a nitrogen (N2) atmosphere to allow the carbon source to initially polymerize. Then, the temperature was raised to 800°C and held under nitrogen protection for 3 hours to achieve carbonization and in-situ nitrogen doping. After cooling to room temperature, the calcined product was obtained. S23. The calcined product was added to a 1.5 mol / L NaOH solution and refluxed at 60°C for 10 h to dissolve the ordered mesoporous silica. After repeated centrifugation and filtration, the product was washed with deionized water until neutral and then vacuum dried to obtain a porous nitrogen-doped carbon support. S30. Preparation of Mn-NC catalyst, including: S31. Weigh 0.5g of the obtained nitrogen-doped ordered mesoporous carbon, add it to 50mL of deionized water, and sonicate it for 30min to form a uniform NC suspension; weigh 0.157g of Mn(Ac)2·4H2O, that is, the mass of the metal element Mn accounts for 7.03% of the mass of the nitrogen-doped ordered mesoporous carbon, dissolve it in 10mL of deionized water, add 2 drops of 0.1mol / L HCl solution, and stir until completely dissolved to obtain a transparent manganese source solution; S32. Slowly add the manganese source solution dropwise to the NC suspension, and magnetically stir at 300 rpm at room temperature for 12 hours to allow the Mn to settle. 2+ The precursor powder is formed by fully coordinating with the N sites of pyridine N, pyrrole N, etc. on the NC surface to form a Mn-N coordination intermediate. After stirring, the intermediate is transferred to a vacuum rotary evaporator and the solvent is evaporated under reduced pressure at 60°C to obtain the precursor powder. S33. Grind the obtained precursor powder evenly, put it into a ceramic boat, place it in a tube furnace, introduce argon gas at a flow rate of 100 mL / min, and continue to purge for 30 min to completely remove the air from the tube furnace. Set and run the heating program: heat to 800℃ at a rate of 5℃ / min, and hold at the temperature for 2 h for high-temperature annealing. S34. After annealing, turn off the heating device, keep the inert gas continuously flowing in, and let the tube furnace cool naturally to room temperature to obtain a black powdery annealing product. Transfer the cooled black powder to a beaker, add 40 mL of 0.5 mol / L H2SO4 solution, and stir in an 80°C water bath for 6 h. Then filter with a Buchner funnel, and wash the filter residue repeatedly with deionized water until the pH of the filtrate is 7 (tested with pH paper) to ensure that residual acid and impurities are completely removed. Then transfer the filter residue to a vacuum drying oven and vacuum dry at 60°C for 12 h. After grinding, a uniform black powder is obtained, which is the Mn-NC catalyst. S40. Preparation of composite catalysts for fuel cells, including: S41. Weigh 0.2 g of Mn-NC catalyst as the active support and place it in 60 mL of ethylene glycol. Disperse it ultrasonically at room temperature for 40 min to form a uniform black dispersion without agglomeration. Weigh 0.529 g of chloroplatinic acid according to the target Pt mass (loading) accounting for 50% of the mass of the fuel cell composite catalyst. Dissolve it in 15 mL of ethylene glycol and stir until completely dissolved to obtain a Pt precursor solution. Slowly add the Pt precursor solution dropwise to the Mn-NC suspension. After the addition is complete, continue stirring at room temperature for 10 h to obtain a mixture. S42. Using an ice bath to control the system temperature at 1℃, add 0.1mol / L NaOH solution dropwise to the mixture to adjust the pH of the system to 8.2. Then, according to the molar ratio of Pt element to reducing agent NaBH4 of 1:8, prepare NaBH4 aqueous solution and slowly add it dropwise to the mixture to carry out the reduction reaction. Stir continuously during the dropwise addition process. After the dropwise addition is completed, remove the ice bath and continue stirring and reducing at room temperature for 3 hours. S43. After the reduction reaction is complete, centrifuge using a high-speed centrifuge, discard the supernatant, and collect the black solid at the bottom; wash repeatedly with anhydrous ethanol and deionized water five times to thoroughly remove residual Cl. - Na +Impurities such as unreacted reducing agents were removed, and the filtrate was washed until it was neutral. The solid product was then transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours. After thorough grinding, the final composite catalyst powder was obtained.
[0068] Example 3 This embodiment provides a fuel cell composite catalyst, comprising an active support and an active component supported on the active support; the active support is MNC, and the active component includes Pt nanoparticles. The preparation method of this fuel cell composite catalyst includes: S10. Preparation of nitrogen-doped carbon support, including: S11. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol at a molar ratio of 1:4. Quickly pour the imidazole solution into the zinc salt solution, stir at room temperature for 24 h, centrifuge to collect the milky white precipitate, wash with methanol 3 times, and then vacuum dry at 60℃ for 12 h to obtain ZIF-8 powder. S12. ZIF-8 was placed in a tube furnace and calcined at 700°C under an argon (Ar) atmosphere for 3 hours. After natural cooling to room temperature, a black powder pyrolysis product was obtained. S13. Add the pyrolysis product to 0.5M H2SO4, stir at 90℃ for 6h for acid washing, then filter, and wash repeatedly with deionized water until the pH of the filtrate is 7. Then dry under vacuum at 60℃ for 12h to obtain nitrogen-doped carbon support. S20. Preparation of nitrogen-doped ordered mesoporous carbon (NC), including: S21. Dissolve the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in a mixture of deionized water and 2M HCl, and stir at 35°C until completely dissolved; then slowly add tetraethyl orthosilicate, and stir continuously for 24 hours before transferring to a hydrothermal reactor and hydrothermally reacting at 100°C for 48 hours. Then filter, wash with water, and dry sequentially, and calcine in air at 500°C for 4 hours to obtain white powdery ordered mesoporous silica. S22. The nitrogen-doped carbon support obtained earlier was dispersed in deionized water, and the obtained ordered mesoporous silica powder was added. After ultrasonic dispersion, the mixture was stirred for 12 hours to allow the nitrogen-doped carbon support to fully enter the mesoporous channels of silica. After evaporation in a water bath, the precursor / ordered mesoporous silica composite was obtained. The composite was pretreated at 180°C for 2 hours under a nitrogen (N2) atmosphere to allow the carbon source to initially polymerize. The temperature was then raised to 700°C and held under nitrogen protection for 4 hours to achieve carbonization and in-situ nitrogen doping. The product was cooled to room temperature to obtain the calcined product. S23. The calcined product was added to a 1.5 mol / L NaOH solution and refluxed at 60°C for 12 h to dissolve the ordered mesoporous silica. After repeated centrifugation and filtration, the product was washed with deionized water until neutral and then vacuum dried to obtain a porous nitrogen-doped carbon support. S30. Preparation of Mn-NC catalyst, including: S31. Weigh 0.5g of the obtained nitrogen-doped ordered mesoporous carbon, add it to 50mL of deionized water, and sonicate it for 30min to form a uniform NC suspension; weigh 0.126g of Mn(Ac)2·4H2O, that is, the mass of the metal element Mn accounts for 5.64% of the mass of the nitrogen-doped ordered mesoporous carbon, dissolve it in 10mL of deionized water, add 2 drops of 0.1mol / L HCl solution, and stir until completely dissolved to obtain a transparent manganese source solution; S32. Slowly add the manganese source solution dropwise to the NC suspension, and magnetically stir at 300 rpm at room temperature for 12 hours to allow the Mn to settle. 2+ The precursor powder is formed by fully coordinating with the N sites of pyridine N, pyrrole N, etc. on the NC surface to form a Mn-N coordination intermediate. After stirring, the intermediate is transferred to a vacuum rotary evaporator and the solvent is evaporated under reduced pressure at 60°C to obtain the precursor powder. S33. Grind the obtained precursor powder evenly, put it into a ceramic boat, place it in a tube furnace, introduce argon gas at a flow rate of 100 mL / min, and continue to purge for 30 min to completely remove the air from the tube furnace. Set and run the heating program: heat to 850°C at a rate of 5°C / min, and hold at the temperature for 2 h for high-temperature annealing. S34. After annealing, turn off the heating device, keep the inert gas continuously flowing in, and let the tube furnace cool naturally to room temperature to obtain a black powdery annealing product. Transfer the cooled black powder to a beaker, add 40 mL of 0.5 mol / L H2SO4 solution, and stir in an 80°C water bath for 6 h. Then filter with a Buchner funnel, and wash the filter residue repeatedly with deionized water until the pH of the filtrate is 7 (tested with pH paper) to ensure that residual acid and impurities are completely removed. Then transfer the filter residue to a vacuum drying oven and vacuum dry at 60°C for 12 h. After grinding, a uniform black powder is obtained, which is the Mn-NC catalyst. S40. Preparation of composite catalysts for fuel cells, including: S41. Weigh 0.2 g of Mn-NC catalyst as the active support and place it in 60 mL of ethylene glycol. Disperse it ultrasonically at room temperature for 40 min to form a uniform black dispersion without agglomeration. Weigh 0.793 g of chloroplatinic acid according to 60% of the target Pt mass (loading) of the fuel cell composite catalyst, dissolve it in 15 mL of ethylene glycol, and stir until completely dissolved to prepare a Pt precursor solution. Slowly add the Pt precursor solution dropwise to the Mn-NC suspension. After the addition is complete, continue stirring at room temperature for 12 h to obtain a mixture. S42. Using an ice bath to control the system temperature at 0℃, add 0.1mol / L NaOH solution dropwise to the mixture to adjust the pH of the system to 8.6. Then, according to the molar ratio of Pt element to reducing agent NaBH4 of 1:10, prepare NaBH4 aqueous solution and slowly add it dropwise to the mixture to carry out the reduction reaction. Stir continuously during the dropwise addition process. After the dropwise addition is completed, remove the ice bath and continue stirring and reducing at room temperature for 3 hours. S43. After the reduction reaction is complete, centrifuge using a high-speed centrifuge, discard the supernatant, and collect the black solid at the bottom; wash repeatedly with anhydrous ethanol and deionized water five times to thoroughly remove residual Cl. - Na + Impurities such as unreacted reducing agents were removed, and the filtrate was washed until it was neutral. The solid product was then transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours. After thorough grinding, the final composite catalyst powder was obtained.
[0069] Example 4 This embodiment provides a fuel cell composite catalyst, comprising an active support and an active component supported on the active support; the active support is MNC, and the active component includes Pt nanoparticles. The preparation method of this fuel cell composite catalyst includes: S10. Preparation of nitrogen-doped carbon support, including: S11. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol at a molar ratio of 1:4. Quickly pour the imidazole solution into the zinc salt solution, stir at room temperature for 24 h, centrifuge to collect the milky white precipitate, wash with methanol 3 times, and then vacuum dry at 60℃ for 12 h to obtain ZIF-8 powder. S12. ZIF-8 was placed in a tube furnace and calcined at 800°C under an argon (Ar) atmosphere for 2 hours. After natural cooling to room temperature, a black powder pyrolysis product was obtained. S13. Add the pyrolysis product to 0.5M H2SO4, stir at 80℃ for 6h for acid washing, then filter, and wash repeatedly with deionized water until the pH of the filtrate is 7. Then dry under vacuum at 60℃ for 12h to obtain nitrogen-doped carbon support. S20. Preparation of nitrogen-doped ordered mesoporous carbon (NC), including: S21. Dissolve the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in a mixture of deionized water and 2M HCl, and stir at 35°C until completely dissolved; then slowly add tetraethyl orthosilicate, and stir continuously for 24 hours before transferring to a hydrothermal reactor and reacting hydrothermally at 150°C for 24 hours. Then filter, wash with water, dry, and calcine in air at 500°C for 4 hours to obtain white powdery ordered mesoporous silica. S22. The nitrogen-doped carbon support obtained earlier was dispersed in deionized water, and then the obtained ordered mesoporous silica powder was added. After ultrasonic dispersion, the mixture was stirred for 12 hours to allow the nitrogen-doped carbon support to fully enter the mesoporous channels of silica. After evaporation in a water bath, the precursor / ordered mesoporous silica composite was obtained. The composite was pretreated at 160°C for 3 hours under a nitrogen (N2) atmosphere to allow the carbon source to initially polymerize. The temperature was then raised to 900°C and held under nitrogen protection for 3 hours to achieve carbonization and in-situ nitrogen doping. The product was cooled to room temperature to obtain the calcined product. S23. The calcined product was added to a 1 mol / L NaOH solution and refluxed at 60°C for 7 h to dissolve the ordered mesoporous silica. After repeated centrifugation and filtration, the product was washed with deionized water until neutral and then vacuum dried to obtain a porous nitrogen-doped carbon support. S30. Preparation of Fe-NC catalyst, including: S31. Weigh 0.5g of the obtained nitrogen-doped ordered mesoporous carbon, add it to 50mL of deionized water, and ultrasonically disperse it for 30min to form a uniform NC suspension; weigh 0.125g of Fe(Ac)2, that is, the mass of the metal element Fe accounts for 7.98% of the mass of the nitrogen-doped ordered mesoporous carbon, dissolve it in 10mL of deionized water, add 2 drops of 0.1mol / L HCl solution, and stir until completely dissolved to obtain a transparent iron source solution; S32. Slowly add the iron source solution dropwise to the NC suspension, and magnetically stir at 300 rpm at room temperature for 12 hours to allow the Fe... 2+ The precursor powder is formed by fully coordinating with the N sites of pyridine N, pyrrole N, etc. on the NC surface to form Fe-N coordination intermediate. After stirring, it is transferred to a vacuum rotary evaporator and the solvent is evaporated under reduced pressure at 60°C to obtain the precursor powder. S33. Grind the obtained precursor powder evenly, put it into a ceramic boat, place it in a tube furnace, introduce argon gas at a flow rate of 100 mL / min, and continue to purge for 30 min to completely remove the air from the tube furnace. Set and run the heating program: heat to 800℃ at a rate of 5℃ / min, and hold at the temperature for 2 h for high-temperature annealing. S34. After annealing, turn off the heating device, keep the inert gas continuously flowing in, and let the tube furnace cool naturally to room temperature to obtain a black powdery annealing product. Transfer the cooled black powder to a beaker, add 40 mL of 0.5 mol / L H2SO4 solution, and stir in an 80°C water bath for 6 h. Then filter with a Buchner funnel, and wash the filter residue repeatedly with deionized water until the pH of the filtrate is 7 (tested with pH paper) to ensure that residual acid and impurities are completely removed. Then transfer the filter residue to a vacuum drying oven and vacuum dry at 60°C for 12 h. After grinding, a uniform black powder is obtained, which is the Fe-NC catalyst. S40. Preparation of composite catalysts for fuel cells, including: S41. Weigh 0.2g of Fe-NC catalyst as the active support and place it in 60mL of ethylene glycol. Disperse it ultrasonically at room temperature for 40min to form a uniform black dispersion without agglomeration. Weigh 0.352g of chloroplatinic acid according to the target Pt mass (loading) accounting for 40% of the mass of the fuel cell composite catalyst. Dissolve it in 15mL of ethylene glycol and stir until completely dissolved to prepare a Pt precursor solution. Slowly add the Pt precursor solution dropwise to the Fe-NC suspension. After the addition is complete, continue stirring at room temperature for 12h to obtain a mixture. S42. Using an ice bath to control the system temperature at 0℃, add 0.1mol / L NaOH solution dropwise to the mixture to adjust the pH of the system to 8.3. Then, according to the molar ratio of Pt element to reducing agent NaBH4 of 1:8, prepare NaBH4 aqueous solution and slowly add it dropwise to the mixture to carry out the reduction reaction. Stir continuously during the dropwise addition process. After the dropwise addition is completed, remove the ice bath and continue stirring and reducing at room temperature for 3 hours. S43. After the reduction reaction is complete, centrifuge using a high-speed centrifuge, discard the supernatant, and collect the black solid at the bottom; wash repeatedly with anhydrous ethanol and deionized water five times to thoroughly remove residual Cl. - Na + Impurities such as unreacted reducing agents were removed, and the filtrate was washed until it was neutral. The solid product was then transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours. After thorough grinding, the final composite catalyst powder was obtained.
[0070] Example 5 This embodiment provides a fuel cell composite catalyst, comprising an active support and an active component supported on the active support; the active support is MNC, and the active component includes Pt nanoparticles. The preparation method of this fuel cell composite catalyst includes: S10. Preparation of nitrogen-doped carbon support, including: S11. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol at a molar ratio of 1:4. Quickly pour the imidazole solution into the zinc salt solution, stir at room temperature for 24 h, centrifuge to collect the milky white precipitate, wash with methanol 3 times, and then vacuum dry at 60℃ for 12 h to obtain ZIF-8 powder. S12. ZIF-8 was placed in a tube furnace and calcined at 800°C under an argon (Ar) atmosphere for 2 hours. After natural cooling to room temperature, a black powder pyrolysis product was obtained. S13. Add the pyrolysis product to 0.5M H2SO4, stir at 70℃ for 6h for acid washing, then filter, and wash repeatedly with deionized water until the pH of the filtrate is 7. Then dry under vacuum at 60℃ for 12h to obtain nitrogen-doped carbon support. S20. Preparation of nitrogen-doped ordered mesoporous carbon (NC), including: S21. Dissolve the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in a mixture of deionized water and 2M HCl, and stir at 35°C until completely dissolved; then slowly add tetraethyl orthosilicate, and stir continuously for 24 hours before transferring to a hydrothermal reactor and reacting hydrothermally at 180°C for 12 hours. Then filter, wash with water, dry, and calcine in air at 500°C for 4 hours to obtain white powdery ordered mesoporous silica. S22. The nitrogen-doped carbon support obtained earlier was dispersed in deionized water, and then the obtained ordered mesoporous silica powder was added. After ultrasonic dispersion, the mixture was stirred for 12 hours to allow the nitrogen-doped carbon support to fully enter the mesoporous channels of silica. After evaporation in a water bath, the precursor / ordered mesoporous silica composite was obtained. The composite was pretreated at 160°C for 3 hours under a nitrogen (N2) atmosphere to allow the carbon source to initially polymerize. The temperature was then raised to 900°C and held under nitrogen protection for 3 hours to achieve carbonization and in-situ nitrogen doping. The product was cooled to room temperature to obtain the calcined product. S23. Add the calcined product to a 1 mol / L NaOH solution, reflux at 80°C for 6 h to dissolve the ordered mesoporous silica, centrifuge and filter repeatedly, wash with deionized water until neutral, and then vacuum dry to obtain a porous nitrogen-doped carbon support. S30. Preparation of Fe-NC catalyst, including: S31. Weigh 0.5g of the obtained nitrogen-doped ordered mesoporous carbon, add it to 50mL of deionized water, and ultrasonically disperse it for 30min to form a uniform NC suspension; weigh 0.156g of Fe(Ac)2, that is, the mass of the metal element Fe accounts for 9.95% of the mass of the nitrogen-doped ordered mesoporous carbon, dissolve it in 10mL of deionized water, add 2 drops of 0.1mol / L HCl solution, and stir until completely dissolved to obtain a transparent iron source solution; S32. Slowly add the iron source solution dropwise to the NC suspension, and magnetically stir at 300 rpm at room temperature for 12 hours to allow the Fe... 2+ The precursor powder is formed by fully coordinating with the N sites of pyridine N, pyrrole N, etc. on the NC surface to form Fe-N coordination intermediate. After stirring, it is transferred to a vacuum rotary evaporator and the solvent is evaporated under reduced pressure at 60°C to obtain the precursor powder. S33. Grind the obtained precursor powder evenly, put it into a ceramic boat, place it in a tube furnace, introduce argon gas at a flow rate of 100 mL / min, and continue to purge for 30 min to completely remove the air from the tube furnace. Set and run the heating program: heat to 800℃ at a rate of 5℃ / min, and hold at the temperature for 2 h for high-temperature annealing. S34. After annealing, turn off the heating device, keep the inert gas continuously flowing in, and let the tube furnace cool naturally to room temperature to obtain a black powdery annealing product. Transfer the cooled black powder to a beaker, add 40 mL of 0.5 mol / L H2SO4 solution, and stir in an 80°C water bath for 6 h. Then filter with a Buchner funnel, and wash the filter residue repeatedly with deionized water until the pH of the filtrate is 7 (tested with pH paper) to ensure that residual acid and impurities are completely removed. Then transfer the filter residue to a vacuum drying oven and vacuum dry at 60°C for 12 h. After grinding, a uniform black powder is obtained, which is the Fe-NC catalyst. S40. Preparation of composite catalysts for fuel cells, including: S41. Weigh 0.2g of Fe-NC catalyst as the active support and place it in 60mL of ethylene glycol. Disperse it ultrasonically at room temperature for 40min to form a uniform black dispersion without agglomeration. Weigh 0.352g of chloroplatinic acid according to the target Pt mass (loading) accounting for 40% of the mass of the fuel cell composite catalyst. Dissolve it in 15mL of ethylene glycol and stir until completely dissolved to prepare a Pt precursor solution. Slowly add the Pt precursor solution dropwise to the Fe-NC suspension. After the addition is complete, continue stirring at room temperature for 12h to obtain a mixture. S42. Using an ice bath to control the system temperature at 0℃, add 0.1mol / L NaOH solution dropwise to the mixture to adjust the pH of the system to 8.5. Then, according to the molar ratio of Pt element to reducing agent NaBH4 of 1:8, prepare NaBH4 aqueous solution and slowly add it dropwise to the mixture to carry out the reduction reaction. Stir continuously during the dropwise addition process. After the dropwise addition is completed, remove the ice bath and continue stirring and reducing at room temperature for 3 hours. S43. After the reduction reaction is complete, centrifuge using a high-speed centrifuge, discard the supernatant, and collect the black solid at the bottom; wash repeatedly with anhydrous ethanol and deionized water five times to thoroughly remove residual Cl. - Na + Impurities such as unreacted reducing agents were removed, and the filtrate was washed until it was neutral. The solid product was then transferred to a vacuum drying oven and dried under vacuum at 60°C for 12 hours. After thorough grinding, the final composite catalyst powder was obtained.
[0071] Example 6 The difference from Example 1 is that in step S31, the amount of Mn(Ac)2·4H2O is adjusted so that the mass of the metal element Mn as a percentage of the mass of nitrogen-doped ordered mesoporous carbon (i.e., the loading of M) is adjusted from 3.58% to 1%. Apart from the above, the other conditions are exactly the same as in Example 1.
[0072] Example 7 The difference from Example 1 is that in step S31, the amount of Mn(Ac)2·4H2O is adjusted so that the mass of the metal element Mn as a percentage of the mass of nitrogen-doped ordered mesoporous carbon (i.e., the loading of M) is adjusted from 3.58% to 12%. Apart from the above, the other conditions are exactly the same as in Example 1.
[0073] Example 8 The difference from Example 1 is that in step S41, the amount of chloroplatinic acid is adjusted so that the mass (loading) of Pt in the fuel cell composite catalyst is adjusted from 40% to 15%. Apart from the above, the other conditions are exactly the same as in Example 1.
[0074] Example 9 The difference from Example 1 is that in step S41, the amount of chloroplatinic acid is adjusted so that the mass (loading) of Pt in the fuel cell composite catalyst is adjusted from 40% to 65%. Apart from the above, the other conditions are exactly the same as in Example 1.
[0075] Comparative Example 1 A commercially available platinum-carbon catalyst with a platinum content of 40% was used.
[0076] Comparative Example 2 A commercially available platinum-carbon catalyst with a platinum content of 50% is used.
[0077] Comparative Example 3 A commercially available platinum-carbon catalyst with a platinum content of 60% was used.
[0078] Comparative Example 4 The difference from Example 1 is that step S10 is performed to obtain a nitrogen-doped carbon support, but step S20 is not performed (i.e., the nitrogen-doped carbon support is not prepared as nitrogen-doped ordered mesoporous carbon). In step S30, the nitrogen-doped carbon support is used to load the metal element Mn to obtain a manganese-containing support. The manganese-containing support is then applied to step S40 to further load Pt to obtain a composite catalyst. Except for the above, the other conditions are exactly the same as in Example 1.
[0079] Comparative Example 5 The difference from Example 1 is that steps S10 and S20 are performed to obtain nitrogen-doped ordered mesoporous carbon, but step S30 (i.e., the metal element Mn is not loaded on the nitrogen-doped ordered mesoporous carbon) is not performed. The nitrogen-doped ordered mesoporous carbon is applied to step S40 to further load Pt to obtain a composite catalyst. Except for the above, the other conditions are exactly the same as those in Example 1.
[0080] Characterization and Testing I. The catalysts obtained in the examples and comparative examples were tested using a rotating disk electrode: Weigh 6 mg of catalyst into a volumetric flask using a balance. Add 500 μL of water, 1500 μL of isopropanol, and 15 μL of Nafion solution (5 wt%) using a pipette. Place the prepared mixture into an ultrasonic apparatus for ultrasonic dispersion, controlling the ultrasonication time at 30 min per cycle and the temperature at 0℃~5℃, until the dispersion is uniform. Then, add the slurry dropwise onto the glassy carbon electrode surface using a pipette. After the slurry dries, the test electrode preparation is complete. The platinum loading on the glassy carbon electrode tip surface is 20 μg / cm³. 2 The test results are shown in Table 1: Table 1 As can be seen from the data in Table 1 above, through electrical performance characterization, the composite catalysts prepared in Examples 1 to 5 are superior to the commercial platinum-carbon catalysts provided in Comparative Examples 1 to 3 in terms of electrochemical activity and durability. Specifically, the composite catalyst obtained in Example 1 has an electrochemical active area of 67.83 m². 2 / g, with a mass activity of 0.55A / mg. pt At 0.90V, after 30,000 accelerated durability cycles, the electrochemical active area decayed by only 28.96%, and the mass activity decayed by only 32.07%. Comparing Comparative Examples 4 and 5 with Example 1, it was found that without further preparation of nitrogen-doped ordered mesoporous carbon on the nitrogen-doped carbon support, even with Mn and further Pt loading, the resulting catalyst performance was poor. Furthermore, without further Pt loading, using only Mn-loaded nitrogen-doped ordered mesoporous carbon as the catalyst also resulted in poor performance, while Pt loading significantly improved performance, indicating a synergistic effect between Mn and the loaded Pt. Compared to Example 1, the loading amounts of Mn and Pt in the catalysts of Examples 6 to 9 all affected the catalyst performance. In this invention, the preferred mass of metal element M in the active support is 3% to 10% of the mass of NC, and the preferred mass of active component Pt is 20% to 60% of the mass of the active support.
[0081] II. The catalysts obtained in the examples and comparative examples were used to prepare the cathode catalyst layer, with a cathode platinum loading of 0.3 mg / cm³. 2 The anode catalyst layers were all prepared using the commercially available TEC10EA20E catalyst, with a platinum loading of 0.05 mg / cm³. 2 The proton exchange membrane is a Gore-enhanced 18μm type, and the gas diffusion layer is SGL 29BC. Assembled into a single cell for testing, the effective area is 25cm². 2 ; Accelerated durability testing of the catalyst was conducted under the following conditions: oxygen and hydrogen were introduced at a relative humidity (RH) of 100%, both at a flow rate of 0.5 L / min, an inlet pressure of 50 kPa, a cell temperature of 80 °C, a scanning voltage of 0.6 V to 1.0 V, and a scanning speed of 50 mV / s. After 20,000 cycles, the test results are shown in Table 2. Table 2 Based on the data in Table 2, it can be seen from Examples 1-5 and Comparative Examples 1-3 that the single cells prepared with the composite catalyst exhibit excellent electrical performance. This is attributed to the high catalytic activity of Pt nanoparticles and the high MN content. x Synergistic effects of the catalyst sites and the structural advantages of nitrogen-doped carbon supports. Comparing Comparative Examples 4 and 5 with Example 1, it was found that without further preparation of nitrogen-doped ordered mesoporous carbon, even with Mn loading and further Pt loading, the performance of the battery containing this catalyst was poor. Simultaneously, without further Pt loading, using only Mn-loaded nitrogen-doped ordered mesoporous carbon as the catalyst also resulted in poor battery performance, while Pt loading significantly improved battery performance, indicating that MNC as a support and the loaded Pt have a synergistic effect. Compared to Example 1, the loading amounts of Mn and Pt in the catalysts of Examples 6 to 9 all affected the performance of the battery containing this catalyst. In this invention, the preferred mass of metal element M in the active support is 3% to 10% of the mass of NC, and the preferred mass of active component Pt is 20% to 60% of the mass of the active support.
[0082] Therefore, the composite catalyst provided in the embodiments of the present invention has the following advantages: 1) The composite catalyst provided in the example is a mesoporous nitrogen-doped carbon support prepared using mesoporous silica as a template. It has abundant mesopores and a high specific surface area, which not only provides sufficient attachment space for active sites, but also constructs unobstructed mass transfer channels. This can accelerate the diffusion of oxygen from the electrolyte to the active sites, while promoting the discharge of water from the reaction product and avoiding the decrease in catalytic activity caused by the "flooding" phenomenon.
[0083] 2) MN in the composite catalyst provided in the examples x Sites can synergistically enhance each other. MN in MNC x (Mainly M-N4) The active sites have strong electronic interactions with Pt nanoparticles, which can optimize the d-band center of Pt, weaken the adsorption strength of oxygen-containing intermediates (such as OOH*, OH*) on the Pt surface in the ORR reaction, reduce the reaction energy barrier, and accelerate the reaction process; at the same time, MN x The site itself also possesses certain ORR catalytic activity, which can assist Pt in completing the oxygen reduction reaction and further improve the overall catalytic efficiency.
[0084] 3) The active sites of the composite catalyst provided in the examples are not easily aggregated or lost. The nitrogen functional groups on the MNC surface can form a strong interaction with Pt nanoparticles, firmly anchoring the Pt particles to the support surface and effectively inhibiting the migration, aggregation, and dissolution loss of Pt particles during the reaction process; at the same time, MN x The sites exist in an atomically dispersed form, are tightly bound to the carbon skeleton, and are not easily detached, further enhancing the long-term stability of the catalyst.
[0085] 4) Pt is a precious metal and its price is high. Its usage is a key factor restricting the commercialization of fuel cells. The composite catalyst provided in this embodiment of the invention significantly reduces the amount of Pt used through synergistic effect, balancing activity and economy.
[0086] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0087] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0088] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A composite catalyst for fuel cells, characterized in that, The active support includes an active carrier and an active component loaded on the active carrier; the active carrier includes MNC, wherein NC represents nitrogen-doped ordered mesoporous carbon having coordinateable N sites, M represents a metal element loaded on the nitrogen-doped ordered mesoporous carbon by coordination with the N sites, and M includes Mn and / or Fe; the active component includes platinum and / or an alloy formed of platinum and a transition metal.
2. The fuel cell composite catalyst according to claim 1, characterized in that, The coordinable N sites include pyridine N and / or pyrrole N; Preferably, the mass of metal element M in the active carrier accounts for 3% to 10% of the mass of NC; Preferably, the active component accounts for 20% to 60% of the mass of the fuel cell composite catalyst.
3. A method for preparing the fuel cell composite catalyst according to claim 1 or 2, characterized in that, include: The MNC and the active component raw material are first mixed in the liquid phase to obtain a mixture; the active component raw material includes a platinum source, or includes a platinum source and a transition metal source that forms an alloy with platinum; The reducing agent is mixed with the mixture to carry out a reduction reaction, thereby obtaining a fuel cell composite catalyst.
4. The method for preparing the fuel cell composite catalyst according to claim 3, characterized in that, The preparation method includes: MNC is dispersed in the first dispersant to obtain a dispersion; The active ingredient raw material is dissolved in the first solvent to prepare an active ingredient raw material solution; The active ingredient raw material solution is added dropwise to the dispersion for a second mixing to obtain the mixture; Preferably, the first dispersant comprises ethylene glycol; Preferably, the first solvent comprises ethylene glycol; Preferably, before the reduction reaction, the temperature is adjusted to 0℃~5℃ and the pH is 8~9; Preferably, the reducing agent includes sodium borohydride; Preferably, the ratio of the molar amount of the reducing agent to the sum of the molar amounts of platinum and transition metal elements that form alloys with platinum in the mixture is (8~10):
1. Preferably, the transition metal element of the transition metal source includes at least one of cobalt, nickel, iron, chromium, palladium, manganese, or copper.
5. The method for preparing the fuel cell composite catalyst according to claim 3 or 4, characterized in that, The method for preparing the MNC includes: Nitrogen-doped ordered mesoporous carbon with coordinateable N sites is provided, denoted as NC; The NC source and the metal M source are mixed in the liquid phase to carry out a coordination reaction and generate a precursor. The precursor was subjected to high-temperature annealing to obtain the annealed product; The annealed product was subjected to acid washing, water washing and drying to obtain MNC.
6. The method for preparing the fuel cell composite catalyst according to claim 5, characterized in that, The method for preparing the MNC includes: The NC and the second dispersant are mixed in a fourth process to obtain a suspension; Prepare an aqueous solution of the metal M source; The aqueous solution of source M is added dropwise to the suspension for a fifth mixing, thereby carrying out the coordination reaction; Preferably, the second dispersant comprises water; Preferably, the metal M source includes an iron source and / or a manganese source; the iron source includes at least one of ferric chloride, ferrous acetate, or ferric nitrate; the manganese source includes at least one of manganese chloride and / or manganese acetate. Preferably, the aqueous solution of source M further includes 1 to 3 drops of 0.01 mol / L to 0.5 mol / L hydrochloric acid; Preferably, the coordination reaction is carried out at a temperature of 15℃ to 35℃ for 6 hours to 12 hours, and at a stirring rate of 100 rpm to 500 rpm. Preferably, after the coordination reaction is completed, the precursor is evaporated to dryness to obtain the precursor. Preferably, the method of evaporation includes vacuum evaporation at 50°C to 70°C; Preferably, the high-temperature annealing is carried out under an inert atmosphere, wherein the flow rate of the inert atmosphere is 80 mL / min to 120 mL / min, the heating rate is 1℃ / min to 10℃ / min, the holding temperature is 800℃ to 850℃, and the holding time is 1h to 2h. Preferably, the pickling uses a sulfuric acid solution of 0.2 mol / L to 0.8 mol / L; Preferably, the pickling temperature is 70℃~90℃ and the time is 2h~10h.
7. The method for preparing the fuel cell composite catalyst according to claim 5 or 6, characterized in that, Methods for preparing NC include: The first template agent and the silicon source are mixed in the first liquid phase in the sixth stage to carry out a hydrothermal reaction. The hydrothermal product is then calcined in the first stage to obtain ordered mesoporous silica. The ordered mesoporous silica was used as a second template agent and mixed with a nitrogen-doped carbon support in the second liquid phase. The solvent was then evaporated to obtain a composite precursor. The composite precursor is pretreated and then subjected to a second calcination to obtain the calcined product. The calcined product was mixed with an alkaline solution for an eighth mixing process, followed by an etching reaction to remove the second template agent, yielding nitrogen-doped ordered mesoporous carbon.
8. The method for preparing the fuel cell composite catalyst according to claim 7, characterized in that, The first template agent comprises a poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer; Preferably, the solution of the first liquid phase comprises water and hydrochloric acid; Preferably, the sixth mixing temperature is 30℃~40℃, and the time is 18h~36h; Preferably, the hydrothermal reaction is carried out at a temperature of 100℃~150℃ for a duration of 24h~48h. Preferably, the first calcination is carried out in an oxygen-containing atmosphere at a temperature of 300℃~600℃ for 3h~6h. Preferably, the solution of the second liquid phase comprises water; Preferably, the seventh mixing method includes ultrasonic dispersion; Preferably, the pretreatment is carried out under a protective atmosphere at a temperature of 150°C to 180°C for 2 to 3 hours. Preferably, the second calcination is carried out under a protective atmosphere at a temperature of 600℃~900℃ for 2h~5h; Preferably, the alkaline solution comprises a sodium hydroxide solution with a concentration of 1 mol / L to 2 mol / L; Preferably, the etching reaction is carried out at a temperature of 60°C to 80°C for a time of 6 hours to 12 hours, and is followed by reflux treatment.
9. The method for preparing the fuel cell composite catalyst according to claim 7 or 8, characterized in that, The method for preparing the nitrogen-doped carbon support includes: Zinc salt was reacted with imidazole in the third liquid phase to obtain ZIF-8 powder; The ZIF-8 powder was subjected to a third calcination to obtain pyrolysis products; The pyrolysis product was acid-washed to obtain a nitrogen-doped carbon support.
10. The method for preparing the fuel cell composite catalyst according to claim 9, characterized in that, The zinc salt includes zinc nitrate; Preferably, the imidazole comprises 2-methylimidazole; Preferably, the molar ratio of the zinc salt to the imidazole is 1:(3~5); Preferably, the solution of the third liquid phase comprises methanol; Preferably, the third calcination is carried out under argon atmosphere at a temperature of 700℃~900℃; Preferably, the pickling uses 0.1 mol / L to 1 mol / L sulfuric acid, the pickling temperature is 60℃ to 90℃, and the pickling time is 4h to 8h.
11. A catalyst coating film, characterized in that, It includes a proton exchange membrane and a catalyst coating disposed on at least one side of the proton exchange membrane; the catalyst coating contains the fuel cell composite catalyst according to claim 1 or 2, or contains the fuel cell composite catalyst obtained by the preparation method according to any one of claims 3-10.
12. A membrane electrode, characterized in that, Contains the catalyst coating film as described in claim 11.
13. A fuel cell, characterized in that, It contains the membrane electrode as described in claim 12.